Pengaruh Literasi Keuangan, Inklusi Keuangan, Kontrol Diri dan Teman Sebaya terhadap Perilaku Menabung Penggemar K-Pop di Pulau Jawa - Mahra Fairus Fatami Hajar; Yuyun Isbanah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to determine how entrepreneurial leadership affects innovation performance by examining the innovation process in start-up businesses. A questionnaire serves as the research tool for this survey-style study. In particular, research was done on start-up businesses in the East Java area, which had about 119 businesses and an average of 20 employees per business, to study the impact of entrepreneurial leadership on innovation performance as mediated through the innovation process. This study employs a quantitative methodology, with surveys disseminated online and data analyzed using partial least squares (PLS). The study's findings demonstrate that entrepreneurial leadership significantly impacts both innovation performance and the innovation process. This study aims to demonstrate how an entrepreneurial leader may significantly affect business operations, particularly the innovation process and performance of firms, particularly those that are technology-based or can be considered start-ups. Moreover, this research demonstrates that the Innovation process is a mediating factor between Entrepreneurial leadership and Innovation performance. According to this study's findings, there is a link between entrepreneurial leadership, the innovation process, and innovation performance. The purpose of this study is to offer information on or a description of entrepreneurial leadership in start-up companies, especially the innovation, and performance it produces.